Deterministic–Probabilistic Prediction of Forest Fires from Lightning Activity Taking into Account Aerosol Emissions; Atmosphere; Vol. 14 iss. 1 - Baranovskiy N. V. Nikolay Viktorovich (2023, 2023)
Title screen